Tundra Fire Regimes in the Noatak River Watershed, Alaska: 1956-83 - Racine, Charles H.; Dennis, John G.; Patterson III, William A. (ARCTIC, 1985)
The location, cause, frequency, size, rotation times, and seasonal timing of tundra fires in the Noatak River watershed of northwestern Alaska were determined from Bureau of Land Management fire records for 1956-83 and satellite (LANDSAT) 1:1 000 000 scale, black and white, band 7 imagery for 1972-81. Seventy-nine fires that burned 1018 km² were detected during the 28-year period from 1956 to 1983. Most of these occurred on the valley floor below 450 m in close proximity to the Noatak River or its tributaries. However, differences in mean fire size, frequency, and rotation times varied greatly among the six physiographic regions of the watershed. All fires occurred during one of two summertime periods in June and July. The implications of this seasonal timing and comparisons of the fire regimes in the Noatak with those in other areas of northern Alaska are discussed.Key words: arctic tundra, LANDSAT imagery, Brooks Range, fire records, fire history, Alaska, Biosphere Reserves Mots clés: toundra arctique, images LANDSAT, chaîne Brooks, dossiers d'incendies, histoire des incendies, Alaska, réserves de la biosphère